ANALISIS EFISIENSI INPUT PRODUKSI SALAK GULA PASIR DI DESA SIBETAN KABUPATEN KARANGASEM - Mahayana, I Gede; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 5 (2024): Vol.13.No.5. MEI 2024 [307-392], 2024)
The efficiency analysis of salak gula pasir production input in Sibetan Village Karangasem aims to analyze the influence of the number of trees, capital, and labor on the production of salak gula pasir and to analyze the efficiency of using each production input. The research was conducted in Sibetan Village with a sample of 79 salak farmers. The samples were taken using stratified random sampling. Data were collected using a questionnaire and analyzed using multiple linear regression analysis. The results of the study show that the number of trees, capital, and labor have a significant simultaneous effect on the production of salak gula pasir. The number of trees and labor have a positive and significant partial effect on the production of salak gula pasir. Capital has a positive but insignificant effect on the production of salak gula pasir. The efficiency analysis of production input shows that the use of the number of trees and capital is not yet efficient, while the use of labor input is used inefficiently. Increasing the number of trees and capital, as well as optimizing labor hours, can increase the production of salak gula pasir.   keyword : efficiency, production of salak gula pasir, number of trees, capital, labor Klasifikasi JEL: D61, D24, Q23, D24, J21